PERANAN AKUNTAN DALAM PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY PADA RUMAH SAKIT DI WILAYAH KABUPATEN SUMENEP - Syahril Syahril; Dedy Arfiyanto (Fakultas Ekonomi dan Bisnis, 2017)
Accountants have a very big role to encourage companies to get involved in activities that show concern for environmental issues Social or Corporate Social ResponsibilityThe purpose of this study is to determine the role of accountants, especially internal accountants in the implementation of Corporate Social Responsibility Hospital in the District Sumenep. This research is descriptive research with qualitative approach. By using this qualitative Descriptive research, writer use to describe, interpret and describe data that writer get from observation, interview and documentation. The analysis uses an interactive model with three procedures: Data Reduction, Presentation of Data and Drawing Conclusions.The role of internal accountants in the implementation of social activities is needed for corporate social responsibility (Hospital in Sumenep District). Because the involvement of internal accountants is very big influence on the decision-making process related to social problems or Corporate Social Responsibility (Corporate Social Responsibility) Keywords : Internal Accountant, Corporate Social Responsibility, Hospital